ESQ dan Kebutuhan Spiritualitas Civitas Akademik: ESQ and the Spirituality Needs of the Academic Community - Solikin, Asep (Anterior Jurnal, 2013)
The truth is that humans are religious (homoreligius) beings and their fithrah is a spiritual being who always strives to always be in a healthy mental state, so that a happy, inner and inner life. He has the perfect spiritual intelligence potential to achieve "spiritual wellness", namely the happiness of true life as a form of divine gift. For this reason, Guidance and Counseling services as a form of interpersonal relationships should adhere to religious values while helping, directing, and guiding individuals to develop spiritual intelligence to reach meaningful life and complete and integrated happiness. Because religious values are fundamental, absolute, and universal.